Design and Evaluation of Protein-coated Nanoemulsions as PFC-Based Artificial Oxygen Carriers using a DoE Approach - 마윤아 (The Graduate School, Ajou University, 2024)
Artificial oxygen carriers (AOCs) have emerged as transformative biomedical solutions, holding immense promise for advancing healthcare and emergency use. AOCs encompass two primary categories: Hemoglobin-Based Oxygen Carriers (HBOCs), which utilize hemoglobin, and Perfluorocarbon-Based Oxygen Carriers (PFOCs), which use perfluorocarbons. The present research aimed to develop and optimize protein-based PFC-Nanoemulsions (PFC-NEs) using Design of Experiment (DoE) methodologies. The research strategically selected perfluorooctyl bromide (PFOB) as the foundational ingredient and meticulously selected surfactants to effectively stabilize the PFC-NEs. The compatibility of the ingredients was demonstrated through Fourier Transform Infrared Spectroscopy (FT-IR) and Differential Scanning Calorimetry (DSC) studies. Additionally, central composite design (CCD) optimization of protein, surfactant, and PFC compositions guided the development of PFC-NEs AOCs. Notably, this formulation exhibited a particle size (PS) spectrum with 129.5 ± 3.9 nm, a Polydispersity Index (PDI) of 0.172 ± 0.019, and a Zeta-Potential (ZP) of -12.67 ± 1.05 mV, achieving a remarkable oxygen encapsulation concentration level of 100.6 ± 0.4%. Crucially, stability assessments validated the resilience of the formulation, demonstrating sustained stability over 4 months under refrigerated (4°C) storage conditions. The formulation also confirmed non-toxicity on the CT-26 cancer cell line, paving the way for in vivo applications. These findings open new avenues for optimizing PFC-AOCs to enhance oxygen transport in various biomedical applications. They highlight the critical role of DoE approaches in improving the efficacy and stability of these carriers, shaping the future of biomedical innovation. Keywords: Artificial Oxygen Carrier, Protein nanocarrier, Perfluorocarbon, Design of Experiment, Oxygen Release Kinetics|인공 산소 운반체는 의료 및 응급 상황에서 혁신적인 생의학적 솔루션으로 부상하여 엄청난 잠재력을 지니고 있다. 인공 산소 운반체는 두 가지 주요 범주로 나뉜다: 헤모글로빈 기반 산소 운반체와 과불화탄소 기반 산소 운반체이다. 본 연구는 실험 계획법 원칙에 의해 최적화된 단백질 기반 과불화탄소-나노에멀젼을 개발하는 것을 목표로 하였다. 연구에서는 기초 성분으로 퍼플루옥틸 브로마이드를 전략적으로 선정하고, 과불화탄소-나노에멀젼을 효과적으로 안정화시키기 위해 계면활성제를 신중하게 선택하였다. 푸리에 변환 적외선 분광법 및 시차 주사 열량법 연구를 통해 성분의 호환성을 확인하였다. 또한, 실험 계획법 방법론에 의해 단백질:계면활성제 및 과불화탄소 조성의 중심 복합 설계 최적화를 통해 단백질 기반 과불화탄소-나노에멀젼 인공 산소 운반체를 최적화하였다. 이 제형은 129.5 ± 3.9 nm의 입자 크기 범위와 다분산 지수 0.172 ± 0.019및 제타 전위 12.67 ± 1.05 mV를 보였으며, 100.6 ± 1.04%의 퍼플루옥틸 브로마이드 캡슐화 농도를 달성하였다. 특히, 안정성 평가에서는 냉장(4℃) 저장 조건에서 4개월 동안 지속적인 안정성을 입증하였다. 또한, CT-26 암 세포주에서 비독성을 확인하여 in vivo 응용 가능성을 열었다. 이러한 결과는 산소 운반을 향상시키는 과불화탄소-나노에멀젼 인공 산소 운반체의 최적화에 새로운 길을 열어준다. 이들은 이러한 운반체의 효능과 안정성을 향상시키는 데 있어 실험 설계법 접근 방식의 중요한 역할을 강조한다._x000D_ 키워드: 인공 산소 운반체, 단백질 나노운반체, 과불화탄소, 실험 설계법, 산소 방출 동력학
학위논문(석사)--바이오헬스규제과학과,2024. 8
Keywords: Artificial Oxygen Carrier; Design of Experiment; Oxygen Release Kinetics; Perfluorocarbon; Protein nanocarrier